SQL Server Always Encrypted : protecting your data with column encryption - Blinn, Eric (Apress, 2019)
"Master SQL Server's Always Encrypted feature to provide column-level encryption of sensitive data such that only authorized application users can see that data. This video explains how the Always Encrypted feature works and shows how to implement column encryption using best practices. System and database administrators who might otherwise have access to view any data in the database are not able to view data protected through Always Encrypted's feature set. This video begins with an introduction to column encryption as implemented through the Always Encrypted feature, and the use cases for applying that encryption. Then follows an explanation of how exactly the technology works and is implemented in SQL Server. The video then walks you through implementing Always Encrypted column encryption on a new database and again on an existing database. Finally, the video covers how to configure an application to access the encrypted data in a manner that is transparent and convenient for end users of your database applications. What You Will Learn Recognize use cases for the Always Encrypted feature Understand how the feature works technically Generate an encrypted column for a new table Insert data into an encrypted database column Encrypt existing data within a table Identify the relevant encryption certificates Modify an application to access encrypted data Who This Book Is For Database administrators, application developers, and system architects who need to encrypt and protect data in a SQL Server instance. Especially helpful when it must be ensured that database administrators and system administrators do not in any way have access to encrypted data."--Resource description page